DNMT3a‐triggered downregulation of K2p1.1 gene in primary sensory neurons contributes to paclitaxel‐induced neuropathic pain. Issue 8 (5th February 2019) - Mao, Qingxiang; Wu, Shaogen; Gu, Xiyao; Du, Shibin; Mo, Kai; Sun, Linlin; Cao, Jing; Bekker, Alex; Chen, Liyong; Tao, Yuan‐Xiang
Abstract : Antineoplastic drugs induce dramatic transcriptional changes in dorsal root ganglion (DRG) neurons, which may contribute to chemotherapy‐induced neuropathic pain. K2p 1.1 controls neuronal excitability by setting the resting membrane potential. Here, we report that systemic injection of the chemotherapy agent paclitaxel time‐dependently downregulates the expression of K 2p 1.1 mRNA and its coding K2p 1.1 protein in the DRG neurons. Rescuing this downregulation mitigates the development and maintenance of paclitaxel‐induced mechanical allodynia and heat hyperalgesia. Conversely, in the absence of paclitaxel administration, mimicking this downregulation decreases outward potassium current and increases excitability in the DRG neurons, leading to the enhanced responses to mechanical and heat stimuli. Mechanically, the downregulation of DRG K 2p 1.1 mRNA is attributed to paclitaxel‐induced increase in DRG DNMT3a, as blocking this increase reverses the paclitaxel‐induced the decrease of DRG K2p 1.1 and mimicking this increase reduces DRG K2p 1.1 expression. In addition, paclitaxel injection increases the binding of DNMT3a to the K 2p 1.1 gene promoter region and elevates the level of DNA methylation within this region in the DRG. These findings suggest that DNMT3a‐triggered downregulation of DRG K2p 1.1 may contribute to chemotherapy‐induced neuropathic pain. Abstract : What's new? Chemotherapy‐induced peripheral neuropathic pain (CIPNP) limits the dosage and selection of anti‐cancer drugs for patients and can lead to therapy discontinuation. While the mechanism underlying CIPNP remains unclear, two‐pore domain background potassium (K2 p) channels, which influence neuronal activity, likely play a role. Here, in mice, systemic administration of paclitaxel was found to downregulate K2 p1.1 in dorsal root ganglion (DRG) neurons. K2 p1.1 knockdown, mimicking paclitaxel effects, resulted in reduced outward potassium channel current and increased DRG excitability. Elevated expression of the DNA methyltransferase DNMT3a contributed to DRG K2 p1.1 downregulation, suggesting that both DNMT3a and DRG K2 p1.1 are crucial to CIPNP development.